Analisis Bibliometrik Pengembangan Media Pembelajaran Pop Up Book di Madrasah Ibtidaiyah pada Tahun 2019-2024 - Titania Amilia Putri; Santiani (PT. Intelek Cendikiawan Nusantara, 2024)
This research aims to analyse the development of Pop Up Book Learning Media in Madrasah Ibtidaiyah in 2019-2024 using bibliometric computational mapping analysis method. Publish or Perish software was used to collect publication data from the Google Scholar database using the keywords